Saving the sea turtles of Anguilla: Combining scientific data with community perspectives to inform policy decisions. (April 2022) - Soanes, L.M.; Johnson, J.; Eckert, K.; Gumbs, K.; Halsey, L.G.; Hughes, G.; Levasseur, K.; Quattro, J.; Richardson, R.; Skinner, J.P.; Wynne, S.; Mukhida, F.
Abstract: Historic over-exploitation and the more recent threats caused by fisheries by-catch, disease and climate change have left sea turtle populations in the Wider Caribbean at risk of extinction. In 1995, following regional declines in nesting and foraging populations, the island of Anguilla implemented a moratorium on the hunting of turtles. At the request of the Government of Anguilla for scientific data to either support or remove the moratorium, comprehensive population estimates were obtained, and foraging, nesting and migratory movements were examined. In addition, community perspectives on turtles and their protection were assessed. Between 2015 and 18 surveys of 30 nesting beaches estimated low nesting activity with a maximum of 41 hawksbill, 15 green, and 1–2 leatherback turtles nesting in Anguilla annually. The inter-nesting range of hawksbills exhibited high levels of geographic overlap and occurred within 1.5 km of nesting beaches. Migratory tracks of hawksbill turtles traversed through seven exclusive economic zones, two of which allow a legal turtle fishery. Site fidelity was observed in foraging areas of green turtles and genetic analysis revealed population differentiation between green turtle foraging sites in Anguilla and between hawksbill rookeries in Anguilla compared to other Leeward Islands, indicating the individual importance of each foraging and nesting site. The Anguillan public (n = 302) overwhelmingly agreed with the current ban on harvesting sea turtles and considered turtles important for ecotourism. Our work provides a case-study, that can be applied globally, of how scientific research combined with community perspectives can effectively inform policy and ultimately protect endangered species, and highlights that local Governments provided with high quality data in a timely fashion for their policy making timetable are more likely to integrate findings into their decision-making process.